Activation-induced cell death of self-reactive regulatory T cells drives autoimmunity - Badami, Ester (Proc Natl Acad Sci U S A, 2019)
Activation of self-reactive T cells is a major driver to autoimmunity and is suppressed by mechanisms of regulation. In a humanized model of autoimmune thyroiditis, we investigated the mechanism underlying break of tolerance. Here, we found that a human TCR specific for the self-antigen thyroid peroxidase (TPO) is positively selected in the thymus of RAG KO mice on both T effector (T(eff)) and T regulatory (T(reg)) CD4(+)Foxp3(+) cells. In vivo T(eff) are present in all immune organs, whereas the TPO-specific T(reg) are present in all lymphoid organs with the exception of the thyroid-draining lymph nodes. We suggest that the presence of TPO in the thyroid draining lymph nodes induces the activation of T(eff) and the depletion of T(reg) via activation-induced cell death (AICD). Our findings provide insights on the failure of the mechanisms of immune tolerance, with potential implications in designing immunotherapeutic strategies.